Merseyside and Cheshire palliative care network audit and guidelines for managing breathlessness. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Jeffries, Clare; Oates, Susan; Ledson, Martin; Bonwick, Helen; Marley, Kate
Abstract : Background: Merseyside and Cheshire Palliative Care Network (MCPCN) Audit Group was established in 1995. It is a multi-professional group composed of individuals working in palliative care across eight integrated care networks (ICN) in community, hospital and hospice settings. Its objective is to develop standards and guidelines through audit, literature review, expert opinion and group consensus to support healthcare professionals working in palliative care in the region. Breathlessness is a common symptom encountered in palliative care in patients with both malignant and non-malignant conditions. Aims: To audit the networks performance against previously developed MCPCN standards on managing breathlessness in advanced disease and revise these standards and guidelines. Method: Previously developed guidelines and standards were reviewed. Literature reviews on pharmacological and non-pharmacological treatments for breathlessness in advanced disease were undertaken. Clinical nurse specialists and doctors working in palliative care across the region were sent an e-mail with a web link to an audit proforma to complete for patients they managed with breathlessness over a 3 month period. Literature review, audit findings and review by external expert was presented to the MCPCN and consensus guidelines and standards reached. Results: The treatment of 106 patients from hospital, hospice and community settings across 7 of 8 ICN was audited. Conclusion: Updated MCPCN guidelines on the use of pharmacological (opioids, benzodiazepines, corticosteroids, nebulised medication, oxygen) and non-pharmacological interventions were developed with evidence and recommendations graded. Revised MCPCN standards include: Reversible causes should be identified and treated where appropriate. Consider a trial of relaxation therapy and/or anxiolytics in patients with anxiety and breathlessness. All patients should have access to non-pharmacological interventions. Diamorphine and morphine are opioids of choice in patients unable to swallow unless already taking an alternative strong opioid. Oxygen should be prescribed. Pulse oximetry should be used; prescribe oxygen only if the patient is hypoxic.